Earnings-Based Anomaly, Accrual-Based Anomaly and the Relationship between Them - Gholamreza Karami (Shahid Bahonar University of Kerman, 2015)
Earnings-based anomaly, known as post-earnings announcement drift, could be regarded as delayed price response to earnings information that results in earning abnormal returns. The accrual anomaly refers to the fact that the current level of accruals is negatively related to abnormal returns over the following year, which may result in earning abnormal returns. These two anomalies appear to be related closely in the sense that accruals could be regarded as the primary component contributing to earnings. The aim of this study is to examine these two anomalies in the Iranian capital market, and to explain the relationship between them. In this study a sample of 560 firm-years from the Tehran Stock Exchange in the period of 1388-1391 has been considered. The results show that earnings-based anomaly is different from accrual anomaly. Also, a hedge portfolio trading strategy that takes both forms of market mispricing, generates abnormal returns higher than those based on only unexpected earnings or accruals information